PERBANDINGAN DEWAN PERWAKILAN RAKYAT DI INDONESIA DAN HOUSE OF REPRESENTATIVE DI AMERIKA SERIKAT DALAM MELAKSANAKAN FUNGSI LEGISLASI: Comparison of the Indonesian People's Consultative Assembly and the House of Representatives in the United States in performing legislative functions - Rachmania, Mutiara; Wijiningsih, Ninuk (Faculty of Law, Universitas Trisakti, 2024)
The House of Representatives based on the 1945 Constitution of the Republic of Indonesia has a role as a law-drafting body (legislation). The existence of people's representative institutions in this democratic country is needed to keep people's power from being abused. As a democracy, the United States also has a legislative institution. The bodies that hold legislative functions in the United States constitution are the Senate and the House of Representatives. The problem of this research is to analyze the similarities and differences in the function of legislation owned by the House of Representatives of the Republic of Indonesia and the House of Representatives in the United States This research uses normative legal research methods with descriptive sifay to analyze secondary data, which is then used to draw conclusions through deductive methods. The result of this study is the similarity in the function of legislation, these two institutions both have the function to draft and approve draft laws. The difference in the legislative function of the two is that the DPR has several stages in drafting and approving laws.